Targeted next generation sequencing identifies a genetic spectrum of DNA variants in patients with hemiplegic migraine. (11th October 2019) - Maksemous, Neven; Smith, Robert A; Sutherland, Heidi G; Maher, Bridget H; Ibrahim, Omar; Nicholson, Garth A; Carpenter, Elisabeth P; Lea, Rod A; Cader, M Zameel; Griffiths, Lyn R
Objective: Hemiplegic migraine in both familial (FHM) and sporadic (SHM) forms is a rare subtype of migraine with aura that can be traced to mutations in the CACNA1A, ATP1A2 and SCN1A genes. It is characterised by severe attacks of typical migraine accompanied by hemiparesis, as well as episodes of complex aura that vary significantly between individuals. Methods: Using a targeted next generation sequencing (NGS) multigene panel, we have sequenced the genomic DNA of 172 suspected hemiplegic migraine cases, in whom no mutation had previously been found by Sanger sequencing (SS) of a limited number of exons with high mutation frequency in FHM genes. Results: Genetic screening identified 29 variants, 10 of which were novel, in 35 cases in the three FHM genes ( CACNA1A, ATP1A2 and SCN1A) . Interestingly, in this suspected HM cohort, the ATP1A2 gene harboured the highest number of variants with 24/35 cases (68.6%), while CACNA1A ranked the second gene, with 5 variants identified in 7/35 cases (20%). All detected variants were confirmed by SS and were absent in 100 non-migraine healthy control individuals. Assessment of variants with the American College of Medical Genetics and Genomics guidelines classified 8 variants as pathogenic, 3 as likely pathogenic and 18 as variants of unknown significance. Targeted NGS gene panel increased the diagnostic yield by fourfold over iterative SS in our diagnostics facility. Conclusion: We have identified 29 potentially causative variants in an Australian and New Zealand cohort of suspected HM cases and found that the ATP1A2 gene was the most commonly mutated gene. Our results suggest that screening using NGS multigene panels to investigate ATP1A2 alongside CACNA1A and SCN1A is a clinically useful and efficient method.